2006
DOI: 10.1128/aem.03022-05
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biofilm Formation and Increased Resistance to Antimicrobial Agents and Bacterial Invasion Are Caused by Synergistic Interactions in Multispecies Biofilms

Abstract: Most biofilms in their natural environments are likely to consist of consortia of species that influence each other in synergistic and antagonistic manners. However, few reports specifically address interactions within multispecies biofilms. In this study, 17 epiphytic bacterial strains, isolated from the surface of the marine alga Ulva australis, were screened for synergistic interactions within biofilms when present together in different combinations. Four isolates, Microbacterium phyllosphaerae, Shewanella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
419
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 602 publications
(458 citation statements)
references
References 63 publications
(69 reference statements)
7
419
2
5
Order By: Relevance
“…Thus, in a niche with a specifi ed number of cells, the presence of different species of bacteria can result in a greater quantity of biofi lm, as has been reported previously 12,13 .…”
mentioning
confidence: 64%
“…Thus, in a niche with a specifi ed number of cells, the presence of different species of bacteria can result in a greater quantity of biofi lm, as has been reported previously 12,13 .…”
mentioning
confidence: 64%
“…This configuration explains that bacteria in biofilm show greater resistance to biocides compared to their planktonic forms. Established biofilms can tolerate antimicrobial agents at concentrations of 10-100 times higher than those needed to kill genetically equivalent planktonic bacteria, making biofilms extremely difficult to eradicate (Burmolle 2006, Jefferson 2004, Stoodley 2002.…”
Section: Biofilmmentioning
confidence: 99%
“…For example, Burmolle et al . (2006) showed that a mixed species biofilm achieves significantly more biomass than the monospecies biofilms (Ren et al ., 2015), without the need to input more nutrients. Further, we and others have observed that such mixed communities have heightened tolerance to antimicrobials, chemical stress and predation (Burmolle et al ., 2006; Lee et al ., 2014; Kumar and Ting, 2015).…”
mentioning
confidence: 99%